AURAL REHABILITATION OF CHILDREN WITH PERSISTENT CONDUCTIVE HEARING IMPAIRMENT - L. V. Toropchina; T. A. Polunina; M. M. Polunin ("Paediatrician" Publishers LLC, 2012)
The authors analyzed the issue of children with persistent conductive hearing impairment rehabilitation in cases when traditional prosthetics with parotid and entotic hearing aids is impossible or contra-indicated. The previous and modern methods of rehabilitation as well as the own authors' experience of aural rehabilitation of children with external and middle ear malformations and bilateral chronic suppurative otitis media with the help of bone anchored hearing aids with covered implants are described in the article.